Efficacy and safety of the Russian protease inhibitor narlaprevir at treatment-naive and earlier treated noncirrhotic patients with the 1st genotype chronic hepatitis C (PIONEER study) - M. V. Mayevskaya; V. T. Ivashkin; O. O. Znoyko; Ye. A. Klimova; D. T. Abdurakhmanov; I. G. Bakulin; P. O. Bogomolov; E. Z. Burnevich; M. Yu. Galushko; N. I. Geyvandova; K. V. Zhdanov; Ye. V. Esaulenko; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of investigation. To estimate efficacy and safety of narlaprevir (NVR) with ritonavir (RTV), pegilated interferon (peg-IFN) and ribavirin (RBV) at treatmentnaïve and earlier treated noncirrhotic patients with chronic hepatitis C caused by the 1st virus genotype in double blind placebo-controlled 3rd phase study (PIONEER). Material and methods. The main group received NVR (200 mg od orally) in combination to RTV (100 mg) and pegIFN/RBV for 12 weeks that was followed by peg-IFN/ RBV for 12 weeks. Comparison group received pegIFN/ RBV for 48 weeks, for the first 12 weeks in combination to placebo. Results. The sustained virologic response in 24 weeks after treatment termination (SVR24) in the main group (NVR/RTV, PEG IFN/RBV)) was achieved in 89.1% (163/183) of treatment-naïve and 69.7% (69/99) of earlier treated patients. SVR24 was achieved in 86.5% (32/37) of patients with relapse after previous peg-IFN/ RBV treatment course. The viral load decreased for the mean of 5.3 log10 in 2 weeks and 5.9 log10 in 4 weeks of treatment in the main group vs 1.5 log10 in 2 weeks and 2.5 log10 in 4 weeks in comparison group. In treatment-naïve patients from the main group SVR24 was achieved in 90.8% at initial METAVIR F0-F2 liver fibrosis stage and in 75% at F3 liver fibrosis stage. In those who were previously treated by peg-IFN/RBV, in the main group SVR-24 was attained in 72.6% at liver fibrosis stage F0-F2 and in 53.3% with F3 liver fibrosis stage. NVR/RTV addition to peg-IFN/RBV treatment did not alter safety profile as compared to peg-IFN/RBV therapy. Conclusions. In PIONEER study the narlaprevir combination therapy was characterized by high efficacy, convenience of administration and favorable safety profile.